Aronia (Aronia melanocarpa) phenolics bioavailability in a combined in vitro digestion/Caco-2 cell model is structure and colon region dependent. (November 2017) - Wu, Ting; Grootaert, Charlotte; Voorspoels, Stefan; Jacobs, Griet; Pitart, Judit; Kamiloglu, Senem; Possemiers, Sam; Heinonen, Marina; Kardum, Nevena; Glibetic, Maria; Smagghe, Guy; Raes, Katleen; et al.
Graphical abstract: Highlights: Metabolism and absorption of Aronia phenolics were investigated. Intestinal absorption depends on colon location and phenolic type. Colon matrix may improve the cellular transport of Aronia phenolics. Abstract: Aronia phenolics are considered to be beneficial for cardiovascular health, but are not always bioavailable. In this study, we evaluated the in vitro bioavailability of Aronia juice phenolics by combination of intestinal digestion models with Caco-2 absorption models. First, intestinal luminal stability and microbial metabolism of Aronia phenolics were investigated using two in vitro digestion models: a short-term batch model and a long term dynamic model (SHIME®). Next, diluted digests were directly applied to Caco-2 cells to simulate enterocyte absorption. Three anthocyanins, 5 flavonol glycosides, 5 phenolic acids and epicatechin were quantified at different stages of digestion and absorption. The location of absorption was compound specific, as procyanidins were mainly absorbed in the distal colon while anthocyanins, flavonol glycosides and phenolic acids were absorbed in the proximal intestinal tract. Further, the food matrix present in the colon significantly increased transport without permanent barrier damage.